AtSUC8 and AtSUC9 encode functional sucrose transporters, but the closely related AtSUC6 and AtSUC7 genes encode aberrant proteins in different Arabidopsis ecotypes. - Sauer, Norbert; Ludwig, Andreas; Knoblauch, Alexander; Rothe, Petra; Gahrtz, Manfred; Klebl, Franz (Plant Journal, 2004)
Three members of the Arabidopsis sucrose transporter gene family, AtSUC6-AtSUC8 (At5g43610; At1g66570; At2g14670), share a high degree of sequence homology in their coding regions and even in their introns and in their 5'- and 3'-flanking regions. A fourth sucrose transporter gene, AtSUC9 (At5g06170), which is on the same branch of the AtSUC-phylogenetic tree, shows only slightly less sequence homology. Here we present data demonstrating that two genes from this subgroup, AtSUC6 and AtSUC7, encode aberrant proteins and seem to represent sucrose transporter pseudogenes, whereas AtSUC8 and AtSUC9 encode functional sucrose transporters. These results are based on analyses of splice patterns and polymorphic sites between these genes in different Arabidopsis ecotypes, as well as on functional analyses by cDNA expression in baker's yeast. For one of these genes, AtSUC7 (At1g66570), different, ecotype-specific splice patterns were observed in Wassilewskija (Ws), C24, Columbia wild type (Col-0) and Landsberg erecta (Ler). No incorrect splicing and no sequence polymorphism were detected in the cDNAs of AtSUC8 and AtSUC9, which encode functional sucrose transporters and are expressed in floral tissue. Finally, promoter-reporter gene plants and T-DNA insertion lines were analyzed for AtSUC8 and AtSUC9.